ANALYSIS OF NATIONAL RESEARCH AND INNOVATION AGENCY (BRIN) TRANSFORMATION READINESS TO ACCELERATE NATIONAL RESEARCH AND INNOVATION DEVELOPMENT USING SWOT ANALYSIS - Ilfa Rizki Amelia; Lina Miftahul Jannah (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2022)
Based on Law Number 11 of 2019 concerning the National System of Science & Technology established the National Research and Innovation Agency (BRIN), which oversees the research process from upstream to downstream. BRIN is an integrated institution of various research institutions in Indonesia, including the Indonesian Institute of Sciences (LIPI), the Agency for the Assessment and Application of Technology (BPPT), the National Nuclear Energy Agency (BATAN), and the Institute for Aeronautics and Space (LAPAN) and a combination of other R&D institutions. This paper aims to analyze readiness transformation National Research and Innovation Agency (BRIN) to acceleration development research and innovation national using SWOT Analysis. This study uses descriptive quantitative methods by distributing questionnaires to 32 respondents who work at BRIN. SWOT Analysis uses the IFAS (Internal Factor Strategic) matrix, which describes strength and weakness factors. The EFAS (External Factor Strategic) matrix describes the opportunities and threats. The results show that the weight of the score on the dimension of strength is 1.47, the weight of the score on the dimension of weakness is 1.28, the weight of the score on the dimension of opportunity is 1.58, and the weight of the score on the threat dimension is 1.19. The total value of the average score on the IFAS matrix is 2.75, and the total value of the average score on the EFAS matrix is 2.77 Keywords : BRIN, Innovation, Research, SWOT Analysis